Effects of Silver Carp Antioxidant Peptide on the Lipid Oxidation of Sierra Fish Fillets (Scomberomorus Niphonius) during Frozen Storage. Issue 2 (15th July 2013) - Qiu, Xujian; Chen, Shengjun; Dong, Shiyuan
Abstract Sierra fish fillets were subjected to 1.5% silver carp antioxidant peptide (SAP) solution, 0.5% carnosine solution, 0.02% propyl gallate (PG) solution and distilled water individually for 1 h at 4C and subsequently stored at −18C for 150 days. At regular intervals, the thiobarbituric acid reactive substances (TBARS), conjugated diene (CD) value, free fatty acid content, free fatty acid composition, fluorescence compound and α‐tocopherol were determined. Results showed that SAP could reduce free fatty acid content, CD formation, TBARS value and fluorescence compound significantly (P < 0.05) during the storage. SAP can also prevent the decrease of eicosapentaenoic acid and docosahexaenoic acid and preserve the endogenous α‐tocopherol contents (P < 0.05). The antioxidant activity of SAP was comparable to that of carnosine. Therefore, SAP could be used as an effective natural antioxidant source to prevent lipid oxidation of fish fillets during frozen storage. Practical Applications Lipid oxidation in fatty fish fillets during frozen storage can cause nutrition loss, rancidity, off‐flavor and thus quality deterioration. This study evaluated the antioxidant effects of a natural peptide on sierra fish fillets during frozen storage. Nowadays, consumers prefer natural food without artificial food additives. This natural peptide could be used in the seafood industry to prevent lipid oxidation of fatty fish fillets as an alternative to traditional synthetic antioxidant food additives.